2006
DOI: 10.1073/pnas.0604990103
|View full text |Cite
|
Sign up to set email alerts
|

CDC7 kinase phosphorylates serine residues adjacent to acidic amino acids in the minichromosome maintenance 2 protein

Abstract: Cdc7 is an essential kinase required for the initiation of eukaryotic DNA replication. Previous studies in many species showed that the minichromosome maintenance complex is a major physiological target of this kinase. In this study, we have mapped the sites in human Mcm2 protein that are phosphorylated by Cdc7. The in vitro phosphorylation of several Mcm2 truncated proteins and peptides revealed that Mcm2 contains two major ( 5 S and 53 S) and at least three minor phosphorylation sites ( 4 S, 7 S, and 59 T) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 25 publications
3
116
0
Order By: Relevance
“…Does the priming phosphorylation play a role in DDK target peptide recognition? This possibility is supported by several studies suggesting that DDK can target serines or threonines adjacent to phosphoserine or phosphothreonine (Cho et al 2006;Masai et al 2006;Montagnoli et al 2006;Wan et al 2008). Indeed, a perusal of the sequences of the N terminus of Mcm4 and Mcm6 shows a large number of clusters of Ser/Thr.…”
Section: Function Of Prior Mcm2-7 Phosphorylationsupporting
confidence: 56%
See 2 more Smart Citations
“…Does the priming phosphorylation play a role in DDK target peptide recognition? This possibility is supported by several studies suggesting that DDK can target serines or threonines adjacent to phosphoserine or phosphothreonine (Cho et al 2006;Masai et al 2006;Montagnoli et al 2006;Wan et al 2008). Indeed, a perusal of the sequences of the N terminus of Mcm4 and Mcm6 shows a large number of clusters of Ser/Thr.…”
Section: Function Of Prior Mcm2-7 Phosphorylationsupporting
confidence: 56%
“…Previous studies have shown that DDK phosphorylation of Mcm2 is dramatically increased when it has been previously phosphorylated (Kihara et al 2000;Cho et al 2006;Montagnoli et al 2006). Furthermore, several Mcm2-7 subunits have been shown to be phosphoproteins in G1 cells in vivo Li et al 2007).…”
Section: Prior Phosphorylation Of the Pre-rc Is Required For Ddk To Tmentioning
confidence: 99%
See 1 more Smart Citation
“…As with the yeast protein, vertebrate Cdc7 has a strong preference for Ser or Thr in an acidic context, either produced by adjacent amino acids that are acidic, or else due to an adjacent CDK site that appears to prime phosphorylation by Cdc7 (Masai et al 2000(Masai et al , 2006Cho et al 2006;Montagnoli et al 2006). In the case of Mcm4, isolated fragments from the N-terminal tail are phosphorylated less well than full-length protein, perhaps indicating the presence of a ''docking domain'' analogous to that of budding yeast Mcm4 (Masai et al 2006).…”
Section: Sld2 and Sld3 Are The Major Targets For Cdk During The Initimentioning
confidence: 99%
“…The DDKs phosphorylate multiple subunits of the Mcm2-7 complex to promote activation of the helicase (Tanaka and Araki 2013). MCM phosphorylation by DDKs is highly conserved in eukaryotes, but it appears that the mechanism by which CDKs stimulate initiation in higher eukaryotes has diverged significantly (Masai et al 2000(Masai et al , 2006Cho et al 2006;Montagnoli et al 2006). Most of what is known about the function of CDK in initiation is from studies in yeast.…”
mentioning
confidence: 99%